2020
DOI: 10.1021/acs.energyfuels.9b03521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sodium on the Formation Mechanism and Physicochemical Properties of Coal-Derived Soot

Abstract: Ion-exchanged Na (INa) and adsorbed Na (ANa) concentrations have significant impact on the physicochemical properties of coal-derived aerosol, and product yields of soot and tar. INa effectively reduced tar release during primary pyrolysis, thus reducing soot yield. ANa had no clear effect on primary pyrolysis, but was easier to gasify. During the secondary pyrolysis, lowconcentrated gasified Na promoted aggregation of aromatics to form soot disordered core and increased soot yield. However, at sufficiently h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…The enhanced PAH formation is suggested to be due to the partial oxidation of soot in the secondary flame zone. Furthermore, another recent study on coal-derived soot showed that Na in pyrolysis gas promoted the aggregation of aromatic compounds, potentially through Na + -π interactions to increase the soot yield [15]. In yet another study, it was shown that at low temperatures Na + promoted the aggregation of small PAH molecules, while inhibited the same at higher temperatures (> 1373 K) due to the dominance of catalytic effects [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhanced PAH formation is suggested to be due to the partial oxidation of soot in the secondary flame zone. Furthermore, another recent study on coal-derived soot showed that Na in pyrolysis gas promoted the aggregation of aromatic compounds, potentially through Na + -π interactions to increase the soot yield [15]. In yet another study, it was shown that at low temperatures Na + promoted the aggregation of small PAH molecules, while inhibited the same at higher temperatures (> 1373 K) due to the dominance of catalytic effects [17].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on the influence of potassium and sodium on soot formation in applied systems, such as biomass and coal combustion systems [7,[10][11][12][13][14][15][16][17][18]. For example, addition of potassium has been found to reduce soot concentration [7], diminish particulate matter emissions [10] and improve catalytic activity in soot oxidation process [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that green manufacturing practice and green logistics practice are the crucial performance of green supply chain management and operation and can improve the economic and environmental performance of enterprises at the same time; research on the implementation of green supply chain management in the mining industry focuses on reducing the impact of the whole supply chain rather than the whole organization on the environment. Most Indian mining industries have insufficient understanding of the influencing factors of green supply chain management; Dong et al (2020) [7] pointed out that, in order to make the economy gradually dynamic and improve efficiency, it is essential to use the capabilities, methods, and qualifications of supply chain management to establish an appropriate corporate structure and management mechanism for coordination efforts. Over time, the gradual development of supply chain capability will lead to "snowball effect," and enhancing supply chain capability will have a synergistic effect on enterprises; in the past decades, with the improvement of environmental awareness, consumers and companies have faced greater pressure to reduce the emission of harmful chemicals and implement green practices in the whole process supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We previously studied the effects of different forms of Na (ion-exchangeable state and physical adsorption state) on the formation characteristics of soot during the pyrolysis of Yimin brown coal at 1250 °C, and found that the inhibition of ion-exchangeable Na on soot formation was much stronger than that of physically adsorbed Na . Ion-exchangeable Na could also be released with volatiles in the form of organic bonding, and these organic-bound Na could promote the combination of surrounding carbon atoms with oxygen-containing substances .…”
Section: Introductionmentioning
confidence: 99%